2019
DOI: 10.7498/aps.68.20190671
|View full text |Cite
|
Sign up to set email alerts
|

Influence of momentum ratio and its throttling method on spray characteristics of pintle injector

Abstract: The spray characteristics of a liquid-liquid pintle injector under different momentum ratios are investigated experimentally in this paper. Water is used as a simulant medium for both the fuel and the oxidizer. By increasing the mass flow rate of the oxidizer or reducing the mass flow rate of the fuel, the local momentum ratio is increased from 0.16 to 0.99, wherein the responding total momentum obtained by the former throttling method is relatively high due to the higher mass flow rate of the fluid. The outer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In liquid rocket engines, the atomization of the liquid propellant can promote evaporation, mixing, and combustion. Since the 1980s, researchers from the United States (Dressler and Bauer, 2000;Gamertsfelder et al, 2020), South Korea (Son et al, 2015;Son et al, 2016a;Radhakrishnan et al, 2018), China (Zhang et al, 2014;Fang and Shen, 2017;Chen et al, 2019;Wang et al, 2020), Japan (Sakaki et al, 2015;, and other countries have carried out a lot of investigations on the spray characteristics of pintle injectors, mainly focusing on the angle and the breakup process of the spray, together with size, velocity, mixing features, and other aspects of the droplets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In liquid rocket engines, the atomization of the liquid propellant can promote evaporation, mixing, and combustion. Since the 1980s, researchers from the United States (Dressler and Bauer, 2000;Gamertsfelder et al, 2020), South Korea (Son et al, 2015;Son et al, 2016a;Radhakrishnan et al, 2018), China (Zhang et al, 2014;Fang and Shen, 2017;Chen et al, 2019;Wang et al, 2020), Japan (Sakaki et al, 2015;, and other countries have carried out a lot of investigations on the spray characteristics of pintle injectors, mainly focusing on the angle and the breakup process of the spray, together with size, velocity, mixing features, and other aspects of the droplets.…”
Section: Introductionmentioning
confidence: 99%
“…Two different spray patterns were observed. Chen et al (2019) studied the spray boundary, droplet size distribution, and flow field characteristics under different momentum ratios and found that the spray characteristics were also affected by the local momentum ratio. Fang and Shen (2017) obtained the effects of the structure parameters on SMD, droplet size distribution uniformity index, and spray angle.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the coupling between the heat release rate and the combustion chamber acoustics occurs with the chamber acoustic natural frequencies when TMR is smaller than unity. Cheng et al [7,[25][26][27][28] researched the spray characteristics of pintle injector through cold tests and theoretically derived the prediction formula of its spray cone angle. Fang and Shen [29] adopted the D SMD obtained in cold tests as the initial condition for two-dimensional numerical simulations and studied the effects of various structural parameters on the combustion performance of the LOX/GCH 4 pintle rocket engine thoroughly.…”
Section: Introductionmentioning
confidence: 99%